2004
DOI: 10.1136/thx.2004.022590
|View full text |Cite
|
Sign up to set email alerts
|

Multiple breath inert gas washout as a measure of ventilation distribution in children with cystic fibrosis

Abstract: Background: Multiple breath inert gas washout (MBW) has been suggested as a tool for detecting early cystic fibrosis (CF) lung disease. A study was undertaken to compare the relative sensitivity of MBW and spirometry for detecting abnormal lung function in school age children with CF and to compare MBW results obtained from healthy children in the UK with those recently reported from Sweden. Methods: Forced expiratory volume in 1 second (FEV 1 ) and maximal expiratory flow when 25% of forced vital capacity rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
233
5
20

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(280 citation statements)
references
References 26 publications
22
233
5
20
Order By: Relevance
“…A lot of studies have suggested that LCI has the advantage over FEV 1 to detect CF lung disease in earlier stages [21,36,38,[64][65][66][67][68]. A more sophisticated analysis of the SnIII has revealed the Scond and Sacin, as indices to detect the mechanisms of ventilation inhomogeneity and the location of the different ventilated lung units.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of studies have suggested that LCI has the advantage over FEV 1 to detect CF lung disease in earlier stages [21,36,38,[64][65][66][67][68]. A more sophisticated analysis of the SnIII has revealed the Scond and Sacin, as indices to detect the mechanisms of ventilation inhomogeneity and the location of the different ventilated lung units.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that only PFTs are reliable to diagnose BOS early and may identify potential asymptomatic patients, and that in those who cannot undergo PFT, especially young children, novel alternative techniques such as multiple-breath washout testing needs to be explored. 15,16 As our understanding about the pathophysiology of BOS is improving, and more patients are surviving longer after SCT with GVHD, The National Institutes of Health consensus group recommends consideration of PFTs or spirometry every 3 months during the first year after transplantation in high-risk patients (patients with chronic GVHD). 12 Regular PFTs in the first year after SCT should allow the capture of subtle changes in lung volumes during a period of tapering immunosuppressant agents when most cases of BOS will start to develop and thus allow an opportunity for earlier and most effective intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing change over time and response to intervention is costly and generally relies on traditional spirometry, which is insensitive (30). More complex global lung function tests based on inert gas washout have been suggested to be sensitive to regional lung ventilation heterogeneity in pediatric CF (8,30,31); however, the use of these methods is no more widespread than 3 He MRI and their regional sensitivity is intrinsically less than an imagingbased method. CT and anatomical 1 H MRI have been shown to be sensitive to signs of CF lung disease (12) but neither have been shown to be sensitive to regional mucus shifting following physiotherapy.…”
Section: Discussionmentioning
confidence: 99%